Social Performance Audit : Measuring the Impact of CSR on Company Sustainability - Fitri Dwi Jayanti; Utami Puji Lestari (International Journal of Management Research and Economics, 2025)
Social performance audit and Corporate Social Responsibility (CSR) are important factors in ensuring corporate sustainability, especially for companies listed on the Indonesia Stock Exchange (IDX). Social performance audit functions as an evaluation tool for the social and environmental impacts generated by the company, while CSR plays a role in building positive relationships with stakeholders and improving the company's reputation. This study aims to analyze the effect of social performance audit and CSR on corporate sustainability in order to provide insight for management in strategic decision making. This study uses a quantitative method with a multiple linear regression approach to test the relationship between social performance audit, CSR, and corporate sustainability. Data were obtained from annual reports and sustainability reports of companies listed on the IDX for the past five years. The research sample was selected using a purposive sampling method with certain criteria to ensure the relevance of the data collected. The results of the study indicate that social performance audit and CSR have a positive and significant effect on corporate sustainability. Companies that implement social audits transparently and run effective CSR programs tend to be more sustainable financially, socially, and environmentally. These findings indicate that integrating sustainability strategies into business models can increase competitiveness and investor confidence. This research provides implications for corporate management, investors, and regulators to strengthen social audit and CSR practices to create a more responsible and sustainable business environment